(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article deals with the morphonological characteristics of prefixes, elementary and complex suffixes of verbal derivatives in the Ukrainian language. It examines the morphonologically relevant features of noun, adjective and verb affixes in the Ukrainian language. It was established that the final elements of the verbal stem, which are changing under the influence of formant initials, signals of possible morphonological operations (reduction, consonant and vocal alternations, lengthening of suffix or root morphemes, accent modification) in verbal derivatives.